The Effect of Distraction Therapy on Pain Levels in Patients with Multiple Lumbar Fractures and Nerve Root Injuries in the Seruni Room at Dr Soebandi Hospital, Jember - Mintarum, Azhar; Murtaqib, Murtaqib; Widayati, Nur; Candra, Eka Yufi Septiana (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims : Lumbar fractures increased from 46.8% to 56.0% between 2009 and 2019, causing severe pain and discomfort, a critical nursing issue requiring attention to enhance patient care quality. Methods : the study was conducted in the Seruni Surgical Room, RSUD dr. Soebandi Jember, focusing on a patient with multiple lumbar fractures and nerve root injury. The patient was selected based on inclusion criteria and pain complaints. The researchers provided a distraction technique, involving listening to classical music and imagining positive things to alleviate pain. Results : the research results showed that there was a difference between the pain scale from the first day to the third day. This distraction technique is given according to the patient's needs when the pain felt by the patient appears. Conclusions : Acute pain is a major nursing issue in patients with multiple fractures and nerve injuries, requiring pain management interventions like music distraction therapy to address physical, psychological, cognitive, and social needs. Researchers hope that nurses can apply therapy independently to patients who have pain.